The impact of corporate social responsibility on the cost of bank loans - Goss, Allen; Roberts, Gordon S. (Journal of Banking & Finance, 2011)
This study examines the link between corporate social responsibility (CSR) and bank debt. Our focus on banks exploits their specialized role as delegated monitors of the firm. Using a sample of 3996 loans to US firms, we find that firms with social responsibility concerns pay between 7 and 18 basis points more than firms that are more responsible. Lenders are more sensitive to CSR concerns in the absence of security. We document a mixed reaction to discretionary CSR investments. Low-quality borrowers that engage in discretionary CSR spending face higher loan spreads and shorter maturities, but lenders are indifferent to CSR investments by high-quality borrowers.